FORMAL EDUCATIONAL RELATIONS AND EMPLOYMENT MOTIVATION WITH EMPLOYEE PERFORMANCE LEVEL IN THE SOUTH OF TAPANULI DPRD. NOVEMBER 2008 - Nuradilah, Nuradilah; Riyadi, Slamet (journal of RESIDU, 2017)
This study aims to obtain data and information about the level of formal education, as well as providing employee motivation and employee performance in the Office of the South Tapanuli DPRD Office and to know the relationship of formal education and work motivation to the performance of employees in the South Tapanuli DPRD Office. This research was conducted in South Tapanuli DPRD Office with total sample of 75 people and the instrument used was questionnaire. The validity of the questionnaire was tested using Moment Correlation Technique with a result of 0.14. The data analysis technique used is F test at significant alpha level of 0.05. The results obtained show that the arithmetic F calculate is greater than F-table (18.3> 3.13). With degrees of freedom dk = 72 (n-k-1) k = 2, = 75 at a significant level of 95% and alpha 5%. Thus a hypothesis stating "there is a positive relationship between formal education and work motivation on employee performance in the South Tapanuli DPRD Office" is acceptable. It is clear that if formal education and employee motivation improved, it will be able to improve the performance of employees in Padang Sidempuan Mayor’s Office. Thus, formal education needs to be improved as well as motivation to improve employee performance.